TAGUCHI METHOD PREDICTION OF EDM DIE-SINKING PARAMETERS ON SURFACE INTEGRITY FOR ALUMINIUM COMPOSITE USING COPPER ELECTRODE - Laily, Suraya; Md Ali, Mohd Amran; Nur Izan Syahriah, Hussein; Mohd Razali, Muhamad; Manshoor, Bukhari; Mohd Amri, Lajis; Raja Izamshah , Raja Abdullah; Abu Bakar, Mohd Hadzley; Taufik , Roni Sahroni (Sci.Int.(Lahore), 2014)
This paper investigates the performance of copper electrode on the surface integrity of aluminium alloy LM6 (Al-Sil2) in the electrical discharge machine (EDM) die sinking.The relationship between the machining parameters which is pulse-on time, pulse-off time, peak current and voltage on surface integrity has been investigated. Copper tool of diameter 10mm was chosen as an electrode. Scanning electrone microscope (SEM) was used to observe the microstructure of LM6 after machining process and the average of recast layer (RL). It was found that the current and pulse on time significantly affected the recast layer, while the pulse off time and voltage are the less significant factor that affected the responses. Result shows that increasing the pulse on time, increases the recast layer. Thus, it shows that copper have the capability to cut aluminium alloy LM6 using EDM die sinking.